Characteristics of Retinoblastoma Patients Treated with Transpupillary Thermotherapy from January ? December 2020 in Cicendo National Eye Hospital (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2021)
Introduction: Treatments for retinoblastoma were aimed to preserve the globe and saving the vision. Transpupillary thermotherapy (TTT) has been used to treat several type of small or medium sized tumor, including retinoblastoma. Purpose: To describe the TTT laser properties for retinoblastoma tumor. Methods: Retrospective method was selected from the medical records. Total sampling data were collected from the patients with diagnosis of retinoblastoma who underwent examination under anasthesia and transpupillary thermotherapy laser in Cicendo National Eye Hospital from January to December 2020. The data collected consist of the demographic information, retinoblastoma tumor characteristics, and TTT laser properties. Results: There was eleven eyes from ten patients who underwent TTT session in Cicendo National Eye Hospital from January until December 2020. Majority was male patients with mean age at diagnosis 16.3 ? 17.01 months and mean TTT session 3.54 ? 1.36 for each eye. The mean total laser that applied in every session were 169.25 ? 241.21 times, with mean power 941.35 ? 1894.16 mW, and mean time exposure 1392.89 ? 1349.09 ms. All of the patients were on chemotherapy systemic treatment, with mean frequency 12.2. Ninety percent patients showed regression of the tumor. Conclusion: Majority of the patients retinoblastoma who treated with TTT were male, bilateral tumor, with mean TTT session 3.54 for each eye. All of the patients treated with systemic chemotherapy. Majority of the eye in this study showed tumor regression..